2008
DOI: 10.1071/ap08033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-aminobutyric acid (BABA) on protection againstPhytophthora infestansthroughout the potato crop cycle

Abstract: The protective effect of b-aminobutyric acid (BABA) on two potato cultivars (Bintje and Pampeana) with different levels of horizontal resistance against Phytophthora infestans was investigated during the crop cycle. Plants were treated with BABA 16, 23, 30, 38, 44, 51, 61 or 75 days after emergence. After each application, the percentage of protection and the content of glucanases, chitinases and phenolic compounds were determined in detached leaves. The foliar pretreatment with BABA up to 30 days after emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The lesion sizes were reduced by 40-50% compared to the untreated control, which is in accordance with many earlier studies of BABA induced resistance in potato (Jeun et al 2000;Jakab et al 2001;Cohen 2002;SiAmmour et al 2003;Altamiranda et al 2008). Also in field trials we found an effect of BABA alone, There are few reports on duration of the improved resistance due to BABA treatment but it appear to depend on the pathosystem (see review by Cohen 2002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The lesion sizes were reduced by 40-50% compared to the untreated control, which is in accordance with many earlier studies of BABA induced resistance in potato (Jeun et al 2000;Jakab et al 2001;Cohen 2002;SiAmmour et al 2003;Altamiranda et al 2008). Also in field trials we found an effect of BABA alone, There are few reports on duration of the improved resistance due to BABA treatment but it appear to depend on the pathosystem (see review by Cohen 2002).…”
Section: Discussionsupporting
confidence: 92%
“…As a comparison, full dose of the fungicide Shirlan delayed the infection by 11 days in Bintje and 14 days in Ovatio. Altamiranda et al (2008) found in greenhouse trials no significant protective effect on the highly susceptible cv. Bintje, while in the more resistant cv.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…citri (Sharifi et al, 2011) which is not directly shown antifungal and antibacterial activities. However, it induces a wide variety of defense mechanisms in the plants like accumulation of PR proteins involved in the antimicrobial activity, depending on the pathogen and its host plant (Altamiranda et al, 2008;Sasek et al, 2011). Interestingly, it has been observed that BABA induces resistance in cauliflower, cabbage, brown mustard, sunflower and lettuce against diseases, but it does not induce the accumulation of PR proteins (Silue et al, 2002;Amzalek and Cohen 2007;Kamble and Bhargava 2007;Cohen et al, 2010).…”
mentioning
confidence: 99%